(3JGQjN edhc GdahfL HGdShOGf hCbGdjeg Edi Mce eMeO HGTG SYjO Hf eMeO Ydi HGTGs - (3eLghds; (3GHf Vja Gddg GdMdaGhjs
(3ChdgG (B:s
(3GdMeO ddg eHOF GdNdb heYjOg GdN s
(3Vefg JGQjN GdChdjGA GdPjf XgQJ hdGjJge ai YgO edhc GdahfL HeOjfI SfGQs
(3fbdgG ef WHbGJ GdChdjGA HGdShOGf ddTjN eMeO fhQ Hf Vja GdMdaGhi GdeJhai SfI (B1224 (3g`s
(3hCVGa YdjgG JGQjN edhc GdahfL GdPjf GSJhdhG Ydi HdGO GdShOGf hCNPhgG ef CjOi HdGO Gs
(3fSNI KGfjI s
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdJGQjNs